Patients' Desires and Expectations for Medical Care in Primary Care Clinics - Zemencuk, Judith K (Blackwell Science Inc, 1998)
To explore whether patients' desires for and expectations of medical care differ between the United States and Canada, we surveyed 652 patients and 105 physicians at primary care sites in Michigan and Ontario. Patient desires were similar at both sites, but expectations were higher in Michigan. Michigan physicians gave higher estimates of patient desire than physicians in Ontario. Physicians at both sites, however, similarly underestimated patients' desires. These between-site differences in expectation may reflect differences both in general cultural factors and in patient exposure to different clinical policies within the medical systems.